Research on the antiviral activity of water-soluble melanin from the pharmaceutical chaga mushroom (Inonotus obliquus) against influenza А virus subtypes H5N1, H3N2 and H1N1pdm09 in experiments in vitro - Ekaterina I. Filippova; Elena V. Makarevich; Maria A. Protsenko; Oleg Y. Mazurkov; Tamara V. Teplyakova; Natalya A. Mazurkova (Журнал микробиологии, эпидемиологии и иммунобиологии, 2023)
Introduction. Influenza A virus is the cause of epidemics and pandemics that severely affect the health and socioeconomic status of the world's population. The need to develop new methods of etiotropic therapy, and the increasing ability of viruses to counteract the antiviral drugs makes extremely relevant the search for new pharmacologically active substances and the subsequent study of their medicinal properties.